2018
DOI: 10.3390/polym10060582
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Attenuation of Graphene Modified Thermoplastic Poly(Butylene adipate-co-terephthalate) Nanocomposites

Abstract: With the widespread development and use of electronics and telecommunication devices, electromagnetic radiation has emerged as a new pollution. In this study, we fabricated flexible multifunctional nanocomposites by incorporating graphene nanoplatelets into a soft thermoplastic matrix and investigated its performance in attenuating electromagnetic radiation over frequency ranges of C (5.85–8.2 GHz), X (8.2–12.4 GHz), and Ku bands (12.4–18 GHz). Effects of nanofiller loading, sample thickness, and radiation fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 69 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…However, in each case, equal amount of dispersed solutions was utilized. Thus, in this case, not only component loading but also structural feature of composite affect EMI SE ( Table S1 and Figure 1 , Figure 7 e and Figure S2 ) [ 77 , 81 , 82 ]. Further, the MXene based composite with less thickness generate relatively good EMI SE compare with other composite reported ( Figure 7 e) and the Al and Cu foil show exceptional EMI shielding of approximately 70 dB (~10 μm).…”
Section: Resultsmentioning
confidence: 99%
“…However, in each case, equal amount of dispersed solutions was utilized. Thus, in this case, not only component loading but also structural feature of composite affect EMI SE ( Table S1 and Figure 1 , Figure 7 e and Figure S2 ) [ 77 , 81 , 82 ]. Further, the MXene based composite with less thickness generate relatively good EMI SE compare with other composite reported ( Figure 7 e) and the Al and Cu foil show exceptional EMI shielding of approximately 70 dB (~10 μm).…”
Section: Resultsmentioning
confidence: 99%
“…Glass fiber, glass balls, and a wide of variety of mineral substances are used as reinforcing additive. As far as extending their thermal limits is a concern, the MID research conducted in the recent years has brought to light two main approaches, namely electron-beam crosslinking and the use of the filler system for modifying thermoplastics, which is capable of satisfying higher requirements, particularly those deriving from the production process [ 171 , 172 , 173 , 174 ].…”
Section: Modified Thermoplastics For Midmentioning
confidence: 99%
“…Recently, graphene composites have been found to be one of the most promising candidates for high-performance porous microwave absorbers in ref. [70] because of their 3D conductive network and multiple scattering. A qualified frequency bandwidth (reflection loss <−10 dB) reaches 5.28 GHz covering almost the entire Ku band at 2 mm thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave shielding effectiveness (SE) for X-band (8-12 GHz) and the flexural properties showed that the total SE of the nanocomposites was increased with the positive gradient of MWNT contents. Great efforts have been made to improve the requirements for microwave applications in X-band and new materials are being tested [70,[76][77][78]. Promising results were found and the search for new materials continues.…”
Section: Introductionmentioning
confidence: 99%